P wave dispersion in assessment of dysrhythmia risk in patients with secundum type atrial septal defect and the effect of transcatheter or surgical closure - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2020)
Atrial dysrhythmia is an important cause of mortality and morbidity in patients with atrial septal defect. Increased P wave duration can predict the risk of atrial dysrhythmia. The aim of this study is to evaluate the risk of atrial dysrhythmia by measuring P wave dispersion, and to observe the effect of surgical and transcatheter closure. Sixty-one patients and 30 controls were investigated. In patient group, before and after closure and in control group at the time of presentation, 12-lead electrocardiography records were evaluated. P wave duration and amplitude, P wave axis, PR interval, P wave dispersion, QRS axis, corrected QT interval, and QT dispersion were calculated. The measurements in patient and control groups, measurements before and after closure, and measurements of surgical and transcatheter group were compared. There were 27 patients in surgical group and 34 patients in transcatheter group. In patient group, signs of right heart volume overload were apparent but there was no significant difference in terms of P wave dispersion between two groups. We compared patient group in itself and found that while the use of medication, cardiothoracic index, ratio of right ventricular dilation, and paradoxical movement in interventricular septum were increased, mean age of closure was younger in surgical group. While P wave dispersion decreased in transcatheter group after closure, it increased in surgical group (p = 0.021). In conclusion, atrial septal defects may cause atrial repolarisation abnormalities and this effect persists even after surgical closure. Transcatheter closure in childhood may decrease dysrhythmia risk in long-term follow-up.
Keywords: Atrial septal defect; P wave dispersion; dysrhythmia; transcatheter closure; ADULT PATIENTS; CHILDREN; DURATION; MAXIMUM; ELECTROCARDIOGRAPHY; SURGERY; REPAIR